PERENCANAAN PENDIDIKAN DALAM PERSPEKTIF ISLAM DI ERA DIGITAL - Yal, Syahrial; nofa, Nuararifah; Asmendri, Asmendri; sari, milya (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2025)
Education is a fundamental element in shaping the quality of human resources, which serves as a key determinant of national progress. In an era of globalization and digital transformation characterized by technological disruption and rapid social, political, and economic change, educational planning becomes a strategic instrument to ensure that educational objectives remain relevant, adaptive, and sustainable. This article aims to examine the concept, implementation, and development strategies of educational planning from an Islamic perspective in the digital era. The study employs a qualitative approach through a library research method, analyzing both national and international literature. The findings reveal that effective educational planning requires an integration of rational, moral and spiritual dimensions as emphasized in the Qur’an, particularly in Surah Al-Hasyr:18, which underscores the importance of visionary thinking and future-oriented planning. In the context of digital transformation, Islamic principles of accountability, justice, and social benefit can be implemented through data-based management, teacher competency enhancement, and the utilization of technology to expand access and ensure equity in education quality. Hence, integrating Islamic value into educational planning in the digital age serves as a strategic approach to addressing modern challenges while ensuring sustainable and equitable educational development.